1985
DOI: 10.3109/03008208509152389
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of crosslinking of proteins by glutaraldehyde III. Reaction with collagen in tissues

Abstract: Bovine pericardium, a dense collagenous connective tissue, was crosslinked with glutaraldehyde using different modalities of fixation. The degree of crosslinking was evaluated as a function of the ability of CNBr and pronase to solubilize collagen. Our results suggest that glutaraldehyde fixes primarily the surface of the fibers and creates a polymeric network which hinders the further crosslinking of the interstitium of the fiber. When a low concentration of glutaraldehyde was used, a slow time-dependent cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
87
1
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(94 citation statements)
references
References 18 publications
3
87
1
1
Order By: Relevance
“…The slightly higher values in Td values (around 2.0 °C) observed for BP previously treated with 0.05% GA are in agreement with the exposure of BP to higher GA concentrations that gives rise to more thermal stable materials 14,29 .As shown by the DSC profiles (Figure 1), independent from processing conditions, all resulting materials were homogeneous in the sense that only one thermal transition was observed in all cases ND and apparently no significant changes in the structure of BP crosslinked with GA were induced by the exposure to Glu/borate buffer.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The slightly higher values in Td values (around 2.0 °C) observed for BP previously treated with 0.05% GA are in agreement with the exposure of BP to higher GA concentrations that gives rise to more thermal stable materials 14,29 .As shown by the DSC profiles (Figure 1), independent from processing conditions, all resulting materials were homogeneous in the sense that only one thermal transition was observed in all cases ND and apparently no significant changes in the structure of BP crosslinked with GA were induced by the exposure to Glu/borate buffer.…”
Section: Resultssupporting
confidence: 69%
“…The problems observed with BHV post implantation as a result of the complexicity of GA solutions are: 1) Impermeabilization of BP surfaces resulting from a polymeric network (Figure 1) which hinders the further crosslinking of the interstitium of the fiber leading to the formation chemically heterogeneous material 14 . This is in agreement with the fact that the number of unreacted ε-amino groups decreases with increasing concentrations of GA 15 .…”
Section: Introductionmentioning
confidence: 99%
“…7. However, due to the polymerization of GTA, cross-linking is sometimes restricted to the surface of the device and a heterogeneous cross-linking structure can then occur (Cheung et al, 1984). Additionally, GTA is incorporated into the new linkage and unreacted GTA can cause local incompatibility, inflammation or calcification (Luyn et al, 1995), along with limited cell ingrowth (Jayakrishnan et al;1996) and cytotoxicity (Sisson et al, 2009) even at concentrations of 3.0 ppm after being released into the host as a result of collagen biodegradation.…”
Section: Methodsmentioning
confidence: 99%
“…Although priming with glutaraldehyde solution increases in vitro resin-dentin bond strengths, it may not increase the ultimate tensile strength of dentin as well as do proanthocyanidin and genipin (Bedran-Russo et al, 2007Castellan et al, 2010). Moreover, being common components of fruits, vegetables, and seeds, genipin and proanthocyanidin have an advantage of not producing the toxic effects (Han et al, 2003) that are reported with glutaraldehyde (Cheung et al, 1985).…”
mentioning
confidence: 99%
“…Glutaraldehyde is a dialdehyde cross-linking agent used commonly as a fixative due to its affinity for active nitrogen groups of amino acids (Cheung et al, 1985;Pashley et al, 2001), and it is probably the most common chemical used to stiffen dentin collagen fibrils. Although priming with glutaraldehyde solution increases in vitro resin-dentin bond strengths, it may not increase the ultimate tensile strength of dentin as well as do proanthocyanidin and genipin (Bedran-Russo et al, 2007Castellan et al, 2010).…”
mentioning
confidence: 99%